Solid titanium catalyst as well as preparation method and application thereof
By preparing solid titanium catalysts with high hydrogen adjustment sensitivity, the problem of uneven particle size distribution of ultra-high molecular weight polyethylene micropowder is solved, the particle size index and processing performance of the product are improved, and the performance requirements of lithium battery separators are met.
Patent Information
- Application Number
- CN202411331636.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-14
AI Technical Summary
In the preparation of ultra-high molecular weight polyethylene micropowder, the particle size distribution range is wide, resulting in a large number of agglomerated coarse particles in the product, which reduces the particle size index of the product and affects the performance of the lithium battery separator.
Using a solid titanium catalyst preparation method, the reaction of elemental magnesium with chloroalkanes to form active magnesium halide, and react with alcohol in hydrocarbon solvent, then react with alkoxysilane at a specific temperature, and finally at preload Alkoxysilane was added to the titanium and supplementary reaction to prepare a solid titanium catalyst with high hydrogen adjustment sensitivity.
This catalyst can significantly improve the hydrogen adjustment sensitivity of ultra-high molecular weight polyethylene, reduce hydrogen consumption, reduce production costs, improve the particle size index and processing performance of polyethylene powder, and meet the performance requirements of lithium battery separators.
Smart Images

Figure CN119431632A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and specifically relates to a solid titanium catalyst and a preparation method and application thereof. Background Art
[0002] Very high molecular weight polyethylene (VHMWPE) refers to polyethylene materials with a viscosity average molecular weight in the range of 500,000-1.2 million. It is also a branch of the ultra-high molecular weight polyethylene field. It has the advantages of high impact resistance, extremely high wear resistance, high corrosion resistance, self-lubrication, resistance to environmental stress cracking, safety and hygiene, etc. Very high molecular weight polyethylene is widely used in many fields, such as the preparation of lithium battery separators.
[0003] The mechanical properties and heat resistance of lithium battery separators made of VHMWPE micropowder are better than those of PE / PP microporous membranes. When the short-circuit temperature is too high, it can "melt without collapsing". It also has a low closed-loop temperature, ensuring the safety of lithium batteries. However, the current production of VHMWPE micropowder is limited by the process, and the particle size distribution range of the obtained particles is relatively wide. Due to static electricity, the product contains a large number of agglomerated coarse particles, which reduces the overall particle size index of the product. The presence of large particles can easily lead to the appearance of crystal points on the surface of the membrane, thereby affecting the performance of the lithium battery separator. Generally speaking, the performance parameters of VHMWPE powder, such as relative molecular mass distribution, particle morphology, and particle size distribution, will be affected by factors such as catalysts and polymerization processes, and these performance parameters will affect the processability of polymer powders, thereby affecting product performance. Therefore, the prior art continues to use a catalyst with high hydrogen sensitivity.
[0004] CN110982000A provides a method for preparing a molded body of ultra-high molecular weight ethylene polymer powder. The molded body includes a lithium battery separator. The molded body is prepared using a catalyst generated by the reaction of an organic magnesium compound and titanium tetrachloride. The molar concentration of hydrogen accounts for 6.5% of the gas phase concentration of ethylene. At the same time, in the presence of 1-butene, polyethylene with a molecular weight of 600,000 can be obtained. Obviously, the hydrogen sensitivity is not enough.
[0005] CN115584003A provides a method for preparing polyethylene lithium battery separator. In the presence of comonomer propylene, when the molar concentration of hydrogen is converted to 0.5% of the concentration of ethylene, polyethylene with a molecular weight of 520,000 can be obtained. However, the patent does not report catalytic activity data, and the patent adds propylene comonomer, which increases production costs.
[0006] CN 113831436 A discloses a method for preparing ultra-high molecular weight polyethylene using a non-cyclopentadienyl catalyst. When the ethylene pressure is 0.6 mPa and the hydrogen pressure is 0.1 mPa (converted to a hydrogen molar concentration of 16.6%), polyethylene with a molecular weight of 510,000 can be obtained, and the catalytic activity is reduced from 38,000 times when no hydrogen is added to 13,000 times. The required hydrogen concentration is very high, and the hydrogen adjustment sensitivity is not enough. Summary of the invention
[0007] In order to solve the above problems in the prior art, the present invention aims to provide a solid titanium catalyst and its preparation method and application. The catalyst has high hydrogen regulation sensitivity.
[0008] In order to achieve the above object, according to a first aspect of the present invention, a method for preparing a solid titanium catalyst is provided, which comprises:
[0009] S1, reacting elemental magnesium with chloroalkane to obtain active magnesium halide, and then reacting the active magnesium halide and alcohol in a hydrocarbon solvent at 50 to 180° C. for 0.5 to 5 hours to obtain a magnesium compound solution;
[0010] S2, reacting the magnesium compound solution and alkoxysilane at 20-100° C. to obtain an intermediate product; wherein the alkoxysilane includes ethoxysilane and methoxysilane, and the molar ratio of the ethoxysilane to the methoxysilane is 6-9:1-4; the molar ratio of the alkoxysilane to the magnesium compound is 0.3-0.5:1;
[0011] S3, reacting the intermediate product with a titanium compound at -30 to 10° C. to obtain a preloaded titanium product;
[0012] S4, raising the temperature to 60-130°C within 1-4 hours, then adding the alkoxysilane, and conducting a supplementary reaction for 1-4 hours to obtain the solid titanium catalyst; wherein the molar amount of the additional alkoxysilane is 1 / 10-1 / 2 of the alkoxysilane added in S2.
[0013] The present invention has particularly found that in the preparation of ultra-high molecular weight polyethylene catalysts, if the organosiloxanes as electron donors are mixed and compounded in a certain ratio, the hydrogen sensitivity of the catalyst can be greatly improved. In particular, when used in combination, ethoxysilane is very beneficial for improving the hydrogen sensitivity of the catalyst, while methoxy helps to maintain high catalytic activity. By compounding ethoxysilane and methoxysilane in a certain ratio, a catalyst with high catalytic activity and strong hydrogen sensitivity can be obtained.
[0014] The preparation method of the present invention defines that the composition of alkoxysilane includes ethoxy and methoxy, defines the ratio, and further defines the addition ratio of alkoxysilane in pre-loaded titanium and supplementary reaction, so that the solid titanium catalyst prepared by the present invention has high hydrogen adjustment sensitivity and is suitable for catalytic preparation of ultra-high molecular weight polyethylene with good fluidity and easy processing. The present invention can reduce the amount of hydrogen used and save production costs. The polyethylene powder produced by the present invention has a low ash content, which ensures the high strength of the polyolefin product while ensuring the easy processing characteristics, thereby improving production efficiency.
[0015] In some preferred embodiments of the present invention, the active magnesium halide compound is active magnesium chloride, having the structure (MgCl2)(R1MgCl) a ; wherein R1 is selected from a C1-C12 alkyl group, preferably a C1-C6 alkyl group, such as methyl, ethyl, propyl, n-butyl, and a is 0.02 to 1. For example, a=0.02, 0.05, 0.1, 0.2, 0.5, 0.55, 0.58, 0.59, 0.8, 1.
[0016] In some preferred embodiments of the present invention, the reaction liquid obtained after the reaction in S4 is filtered, washed and dried to obtain the solid titanium catalyst.
[0017] In some preferred embodiments of the present invention, the molecular formula of the alkoxysilane is (R) n Si(OR) 4-n ; Wherein, R is a C1-C12 alkyl or halogenated alkyl, n is an integer of 1-4, and OR is an ethoxy or methoxy group;
[0018] Preferably, the ethoxysilane includes one or a combination of two or more of γ-chloropropyltriethoxysilane, dimethyldiethoxysilane, dipropyldiethoxysilane, diisopropyldiethoxysilane, isobutyldiethoxysilane, dibutyldiethoxysilane, cyclohexylmethyldiethoxysilane, cyclohexylisopropyldiethoxysilane, cyclopentylisobutyldiethoxysilane, cyclopentylisopropyldiethoxysilane, cyclopentylbutyldiethoxysilane, cyclopentylpropyldiethoxysilane, dicyclopentyldiethoxysilane, diphenyldiethoxysilane, phenyltriethoxysilane, methyltriethoxysilane, butyltriethylsilane, isobutyltriethoxysilane and vinyltriethoxysilane;
[0019] Preferably, the methoxysilane includes one or a combination of two or more of γ-chloropropyltrimethoxysilane, dimethyldimethoxysilane, dipropyldimethoxysilane, diisopropyldimethoxysilane, isobutyldimethoxysilane, dibutyldimethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexylisopropyldimethoxysilane, cyclopentylisobutyldimethoxysilane, cyclopentylisopropyldimethoxysilane, cyclopentylbutyldimethoxysilane, cyclopentylpropyldimethoxysilane, dicyclopentyldimethoxysilane, diphenyldimethoxysilane, phenyltrimethoxysilane, methyltrimethoxysilane, butyltrimethoxysilane and isobutyltrimethoxysilane.
[0020] In some preferred embodiments of the present invention, in S3, the preloaded titanium reaction conditions are to react at 20-0°C for 1-3h;
[0021] Preferably, the molar ratio of the titanium compound to the magnesium compound is 2 to 30:1;
[0022] Preferably, the titanium compound includes one or more of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, tetrabutoxytitanium, and tetraethoxytitanium; more preferably, it is titanium tetrachloride.
[0023] In some preferred embodiments of the present invention, in S4, the temperature of the supplementary reaction is 90-110°C;
[0024] Preferably, the molar amount of the alkoxysilane added in S4 is 1 / 5 to 1 / 3 of the alkoxysilane added in S2.
[0025] In some preferred embodiments of the present invention, a crystallization promoter is further added to S2;
[0026] Preferably, the molar ratio of the crystallization promoter to the active magnesium halide is 0.05 to 1:1;
[0027] Preferably, the crystallization promoter is an acid anhydride crystallization promoter; preferably, the crystallization promoter includes one or a combination of two or more of norbornene anhydride, phthalic anhydride, and maleic anhydride.
[0028] In some preferred embodiments of the present invention, in S1, the molar ratio of the active magnesium halide to the alcohol is 1:1 to 5; preferably 1:2 to 3;
[0029] Preferably, the ratio of the active magnesium halide to the hydrocarbon solvent is 1 mol: 0.2-1.0 L;
[0030] Preferably, the hydrocarbon solvent is a C4-C18 aliphatic hydrocarbon, more preferably a C6-C12 aliphatic hydrocarbon;
[0031] Preferably, in S1, the alcohol comprises a C2-C16 fatty alcohol; preferably comprises one or a combination of two or more of ethanol, propanol, butanol, hexanol, 2-methyl alcohol, n-heptanol, isooctyl alcohol, and n-octanol;
[0032] Preferably, in S1, the molar ratio of the ethoxysilane to the methoxysilane is 7-9:1-3.
[0033] According to another aspect of the present invention, a solid titanium catalyst prepared according to the above preparation method is provided.
[0034] In some preferred embodiments of the present invention, the average particle size of the solid titanium catalyst is preferably 1 to 20 microns, more preferably 1 to 10 microns, more preferably 2 to 16 microns, more preferably 2 to 8 microns, and further preferably 2.5 to 3.5 microns. If the average particle size of the solid titanium catalyst is 1 micron or more, there is a tendency to prevent the scattering and adhesion of the obtained ethylene polymer particles. In addition, when the average particle size is 5 microns or less, there is a tendency to prevent the ethylene polymer particles from becoming too large and settling in the polymerization system, and the clogging of the pipeline in the post-treatment process of the ethylene polymer.
[0035] According to another aspect of the present invention, there is provided an ultra-high molecular weight polyethylene prepared by catalysis using the above-mentioned solid titanium catalyst, wherein the preparation conditions include: a reaction temperature of 40 to 90° C., preferably 60 to 85° C., and a pressure of 0.1 to 1 MPa, preferably 0.2 to 0.8 MPa;
[0036] The ultra-high molecular weight polyethylene satisfies one or a combination of two or more of the following conditions:
[0037] The viscosity average molecular weight is 200,000-1,000,000; more preferably 300,000-800,000;
[0038] The intrinsic viscosity is 4 to 10 dl / g;
[0039] Ash content is 150-200ppm;
[0040] Bulk density is 0.45~0.60g / cm 3 ; Further preferably, the bulk density is 0.45 to 0.5 g / cm 3 ;
[0041] The average particle size is 100 to 200 μm; more preferably, the average particle size is 110 to 150 μm; more preferably, the average particle size is 110 to 125 μm.
[0042] In some preferred embodiments of the present invention, the preparation conditions of ultra-high molecular weight polyethylene include: the mass ratio of ethylene to hydrogen is 3000:1 to 4000:1, and the stirring speed is 200 to 1000 rpm.
[0043] In some preferred embodiments of the present invention, the method for preparing ultra high molecular weight polyethylene further comprises:
[0044] Provided is a catalyst combination system, which comprises the solid titanium catalyst and a co-catalyst of the present invention, wherein the co-catalyst is a metal organic compound, preferably an organoaluminum compound R 3-n A1X n , wherein X is a halogen, R is a C1-C12 alkyl group, and n is an integer of 0-2; wherein the molar ratio of the aluminum in the co-catalyst to the titanium in the catalyst active component is 10-300, preferably 20-150, and more preferably 30-80.
[0045] The ultra-high molecular weight polyethylene of the present invention has excellent fluidity, high bulk density, fine particle size and excellent comprehensive performance. In particular, in lithium-ion secondary battery separators, the stability of battery characteristics is very important, and the present invention can meet the performance requirements of separator materials.
[0046] In some preferred embodiments of the present invention, in the ultra-high molecular weight polyethylene, the proportion of particles with a diameter exceeding 350 microns is less than 2 wt %.
[0047] In some preferred embodiments of the present invention, the particle size distribution (d90-d10) / d50 of the ultra-high molecular weight polyethylene is 0.6-1.
[0048] According to another aspect of the present invention, a lithium battery separator is provided, which is obtained by processing the above-mentioned ultra-high molecular weight polyethylene.
[0049] According to another aspect of the present invention, a lithium battery is provided, which comprises the above-mentioned lithium battery separator. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is the SEM morphology of the solid titanium catalyst prepared in Example 1.
[0051] Figure 2 This is the SEM morphology of the solid titanium catalyst prepared in Example 3.
[0052] Figure 3 This is the SEM morphology of No. 7 polyethylene product.
[0053] Figure 4 Performance test results of the catalyst and the corresponding ultra-high molecular weight polyethylene. DETAILED DESCRIPTION
[0054] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0055] The test method is as follows:
[0056] The intrinsic viscosity was measured according to ASTM D4020-05 using a high-temperature Ubbelohde viscometer method, Mv = 5.34 × 10 4 (η) 1.37 .
[0057] The polyethylene particle size was measured by a laser particle analyzer (Mastersizer X, Malvern), where D10, D50 and D90 distributions refer to the size of particles at each percentage of 10, 50 and 90. D50 is defined as the average particle distribution, and the particle size distribution is defined as (d90-d10) / d50.
[0058] Bulk density is tested according to GB / T1636-2008;
[0059] Ash content is tested according to GB / T9345.5-2010;
[0060] The thickness of the diaphragm is tested according to GB / T6672-2001;
[0061] Air permeability is tested according to GB / T458-2008;
[0062] Porosity and surface density are tested according to GB / T24218.1-2009;
[0063] Tensile strength is tested according to GB / T1040.3-2006;
[0064] The puncture strength is tested according to GB / T23318-2009.
[0065] The active MgCl2 carrier used in the following examples was prepared by the following method:
[0066] Take 0.2 mol of magnesium powder and place it in a 500 mL three-necked flask replaced with nitrogen, add 100 mL of decane, 0.02 g of iodine and 20 mL of n-butyl chloride; heat to 75 ° C and stir to activate for 2 hours, add 1 mol of dry n-butyl chloride (obvious reaction can be observed), continue to react for 3 hours, filter, wash the obtained solid with hexane and dry it to obtain an active MgC12 carrier. Elemental analysis shows that the composition of the prepared active MgC12 carrier is: (MgCl2)(BuMgCl) 0.59 .
[0067] Example 1
[0068] This embodiment provides a method for preparing a solid titanium catalyst, which comprises:
[0069] S1, 0.5 mol (in terms of Mg) of active MgC12 carrier, 200 mL of decane and 260 mL of isooctyl alcohol (1.67 mol) were heated to 130° C. and reacted for 60 minutes to obtain a magnesium compound solution;
[0070] S2, cooling to 65° C., adding 0.167 mol of alkoxysilane (the molar ratio of γ-chloropropyltriethoxysilane / γ-chloropropyltrimethoxysilane is 9:1) and 0.15 mol of norbornene anhydride at this temperature, and continuing the reaction for 60 minutes to obtain an intermediate product;
[0071] S3, after cooling, slowly add dropwise to 2000mL TiC14 at 0°C for 90 minutes, with a stirring speed of 1000 rpm, and keep the temperature at 0°C for 60 minutes after the addition is completed;
[0072] S4, slowly raise the temperature to 110°C over 120 minutes, add 0.05 mol of the same alkoxysilane at this temperature, continue the reaction for 120 minutes, then stop stirring, allow the solid titanium catalyst particles to settle quickly, and filter out the solid product hot after the reaction is completed. Wash with hexane, 400 mL each time, until the filtrate is basically colorless, wherein the free titanium content is less than 0.3 mg / mL, and dry to obtain a solid titanium catalyst.
[0073] The obtained solid titanium catalyst is spherical, with elemental analysis of Ti: 4.15%, Mg: 15.5%, Si: 1.06%, and an average particle size of 3.0 μm.
[0074] The SEM images of the catalyst are shown in Figure 1 , Hitachi Regulus8100 test.
[0075] Example 2
[0076] This embodiment provides a method for preparing a solid titanium catalyst, which comprises:
[0077] S1, 0.5 mol (in terms of Mg) of active MgC12 carrier, 200 mL of decane and 152 mL of n-butanol (1.67 mol) were heated to 130° C. and reacted for 60 minutes to obtain a magnesium compound solution;
[0078] S2, cooling to 65° C., adding 0.167 mol of alkoxysilane (the molar ratio of methyltriethoxysilane / dimethyldimethoxysilane is 8:2) and 0.15 mol of norbornene anhydride at this temperature, and continuing the reaction for 60 minutes to obtain an intermediate product;
[0079] S3, after cooling, slowly add dropwise to 2000mL TiC14 at 0°C for 90 minutes, with a stirring speed of 1000 rpm, and keep the temperature at 0°C for 60 minutes after the addition is completed;
[0080] S4, slowly heat up to 110°C over 120 minutes, add 0.05 mol of the same silane electron donor at this temperature, continue the reaction for 120 minutes to obtain a solid titanium catalyst, stop stirring, allow the solid titanium catalyst particles to settle quickly, and filter out the solid product hot after the reaction is completed. Wash with hexane, 400 mL each time, until the filtrate is basically colorless, wherein the free titanium content is less than 0.3 mg / mL, and dry to obtain a solid titanium catalyst. The catalyst is spherical, and the elemental analysis is: Ti: 4.23%, Mg: 15.1%, Si: 1.05%.
[0081] Example 3
[0082] The difference from Example 1 is that the amounts of alkoxysilane added twice are 0.160 mol and 0.012 mol respectively. Elemental analysis: Ti: 4.06%, Mg: 15.8%, Si: 1.08%, average particle size is 2.9 μm. The SEM image of the catalyst is shown in Figure 2 , tested by Hitachi Regulus8100.
[0083] Example 4
[0084] The difference from Example 1 is that the molar ratio of γ-chloropropyltriethoxysilane / γ-chloropropyltrimethoxysilane is 6:4. Elemental analysis: Ti: 3.97%, Mg: 16.7%, Si: 1.18%.
[0085] Example 5
[0086] The difference from Example 2 is that the amounts of alkoxysilane added twice are 0.152 mol and 0.020 mol respectively. Elemental analysis: Ti: 4.09%, Mg: 15.2%, Si: 1.13%.
[0087] Example 6
[0088] The difference from Example 2 is that the ratio of methyltriethoxysilane to dimethyldimethoxysilane is 7:3. Elemental analysis: Ti: 4.18%, Mg: 15.4%, Si: 1.20%.
[0089] Example 7
[0090] The difference from Example 1 is that the reaction temperature in step S4 is changed from 110° C. to 90° C. Element analysis: Ti: 3.87%, Mg: 16.1%, Si: 1.01%, and the average particle size is 3.2 μm.
[0091] Example 8
[0092] The difference from Example 1 is that the reaction temperature in step S4 is changed from 110° C. to 120° C. Element analysis: Ti: 4.33%, Mg: 15.1%, Si: 1.13%, and the average particle size is 3.0 μm.
[0093] Example 9
[0094] The difference from Example 1 is that the electron donor is cyclohexylmethyldiethoxysilane / cyclohexylmethyldimethoxysilane (molar ratio is 9:1). Elemental analysis: Ti: 4.33%, Mg: 15.1%, Si: 1.13%, and the average particle size is 3.2 μm.
[0095] Example 10
[0096] The difference from Example 1 is that the electron donor is cyclohexylisopropyldiethoxysilane / cyclohexylisopropyldimethoxysilane (molar ratio is 9:1). Elemental analysis: Ti: 4.26%, Mg: 15.3%, Si: 1.09%, and the average particle size is 3.1 μm.
[0097] Comparative Example 1
[0098] 0.5 mol (in terms of Mg) of active MgC12 carrier, 200 mL of decane and 260 mL of isooctyl alcohol (1.67 mol) were heated to 130°C for 60 minutes, cooled to 65°C, 0.172 mol of γ-chloropropyltrimethoxysilane and 0.15 mol of norbornene anhydride were added at this temperature, and the reaction was continued for 60 minutes, and then cooled to room temperature. Then, the mixture was slowly added dropwise to 2000 mL of TIC14 at 0°C for 90 minutes, with a stirring speed of 1000 rpm. After the addition was completed, the temperature was kept at 0°C for 60 minutes, and then the temperature was slowly raised to 110°C for 120 minutes. At this temperature, 0.05 mol of the same alkoxysilane was added, and the reaction was continued for 120 minutes to obtain a solid titanium catalyst. After stopping the stirring, the solid titanium catalyst particles were quickly precipitated, and the solid product was filtered out hot after the reaction was completed. Wash with hexane, 400 mL each time, until the filtrate is basically colorless, and the free titanium content is less than 0.3 mg / mL, and then dry to obtain a solid titanium catalyst. The catalyst is spherical, and the elemental analysis is: Ti: 4.01%, Mg: 16.3%, Si: 1.03%, and the average particle size is 3.3 μm.
[0099] Comparative Example 2
[0100] The same as Example 1, except that the amount of alkoxysilane added twice is the same, both 0.086 mol. Element analysis: Ti: 4.03%, Mg: 15.9%, Si: 1.03%, average particle size 3.2 μm.
[0101] Comparative Example 3
[0102] The same as Example 1, except that the siloxane used is single dimethyldimethoxysilane. Elemental analysis: Ti: 4.10%, Mg: 15.6%, Si: 1.04%, average particle size is 3.2 μm.
[0103] A special high molecular weight polyethylene, the preparation method of which comprises:
[0104] In a 4.0 cubic meter stainless steel autoclave, after nitrogen replacement, 2.8 cubic meters of dehydrated hexane (water content <10ppm), triethylaluminum hexane solution (according to AlTi molar ratio of 30), and 20g of the solid titanium catalyst in the above-mentioned embodiment or comparative example are added in sequence, the stirring speed is 500 rpm, the temperature is raised to 50°C, ethylene is introduced until the autoclave pressure is 0.5Mpa (gauge pressure), at 85°C, the autoclave pressure is maintained at 0.5Mpa, hydrogen is continuously introduced, and a certain ratio of ethylene / hydrogen is controlled. The polymerization reaction is carried out for a certain time. When the polymerization amount reaches 800kg, the pressure is absorbed and the temperature is lowered to room temperature. After the material is discharged and dried, an ultra-high molecular weight polyethylene product is obtained.
[0105] The polyethylene samples corresponding to the synthesis under different ethylene / hydrogen conditions in each embodiment or comparative example are numbered (eg Figure 4 ). Figure 3 This is the electron microscope image of the polyethylene sample No. 7. Figure 3 It can be found that the polyethylene powder prepared by the catalyst developed in the present invention is spherical and has a porous structure. This porous structure is very conducive to dissolution processing and improves the production efficiency of the diaphragm.
[0106] The performance of the catalyst and the corresponding ultra-high molecular weight polyethylene were tested. Figure 4 Among them, GUR4116 is a standard sample purchased from Celanese Corporation.
[0107] from Figure 4It can be seen from the data that the use of mixed electron donors (alkoxysilanes) can have a better viscosity index while maintaining the activity of the catalyst, that is, greatly improve the hydrogen sensitivity of the catalyst. Taking Example 3 as an example, when no hydrogen is added, the molecular weight reaches 2.3629 million, and the characteristic viscosity can reach 15.9dl / g, which has reached the range of ultra-high molecular weight polyethylene; and when the ethylene / hydrogen mass ratio reaches 4000:1, the characteristic viscosity is less than 5.4dl / g, which belongs to the range of ultra-high molecular weight polyethylene, and each performance can meet the requirements of lithium battery separators; and when the ethylene / hydrogen mass ratio is further reduced to 3500:1 (the molar concentration of hydrogen accounts for 0.4% of ethylene), the characteristic viscosity is 4.9dl / g, and all data are basically consistent with the standard sample GUR4116, which meets the requirements of lithium battery separator materials. In Comparative Example 1, which uses a pure ethoxy electron donor, the presence of ethoxy groups makes it more sensitive to hydrogen regulation, but its catalytic activity is reduced, resulting in the polymer ash content exceeding 200ppm and being unable to be used for lithium battery separators. When the ethylene / hydrogen mass ratio is further increased to 6000:1, when the molecular weight reaches 658,000, the ash content still does not meet the ash content requirement of lithium battery separators (<200ppm). In Comparative Example 3, which uses a pure methoxy electron donor, although the catalytic activity is very high, the hydrogen regulation sensitivity is very poor due to the absence of ethoxy groups. When the ethylene / hydrogen mass ratio reaches 1000:1, a polymer product with a suitable viscosity index and easy processing cannot be obtained. This application has strict restrictions on the amount of mixed electron donors added. Only when the amount added is controlled within a certain range can the high hydrogen regulation sensitivity catalyst of the present invention be prepared. For example, after adjusting the addition method of the two electron donors in Comparative Example 2, not only the catalyst activity decreases, but also the hydrogen regulation sensitivity of the catalyst is reduced. The target polymer product cannot be obtained within the same ethylene / hydrogen mass ratio range.
[0108] No. 7, 16 ultra-high molecular weight polyethylene and GUR4116 were selected and sent to relevant lithium battery separator companies for lithium battery separator testing. The results are shown in Table 1.
[0109] Table 1
[0110]
[0111] It can be found from the data in Table 1 that the lithium battery separator of the present invention has good comprehensive performance.
Claims
1. A method for preparing a solid titanium catalyst, characterized in that: include: S1, reacting elemental magnesium with chloroalkane to obtain active magnesium halide, and then reacting the active magnesium halide and alcohol in a hydrocarbon solvent at 50 to 180° C. for 0.5 to 5 hours to obtain a magnesium compound solution; S2, reacting the magnesium compound solution and alkoxysilane at 20-100° C. to obtain an intermediate product; wherein the alkoxysilane includes ethoxysilane and methoxysilane, and the molar ratio of the ethoxysilane to the methoxysilane is 6-9:1-4; the molar ratio of the alkoxysilane to the magnesium compound is 0.3-0.5:1; S3, reacting the intermediate product with a titanium compound at -30 to 10° C. for 1 to 6 hours to obtain a preloaded titanium product; S4, raising the temperature to 60-130°C within 1-4 hours, then adding the alkoxysilane, and conducting a supplementary reaction for 1-4 hours to obtain the solid titanium catalyst; wherein the molar amount of the additional alkoxysilane is 1 / 10-1 / 2 of the alkoxysilane added in S2.
2. The preparation method according to claim 1, characterized in that: The molecular formula of the alkoxysilane is (R) n Si(OR) 4-n ; Wherein, R is a C1-C12 alkyl or halogenated alkyl, n is an integer of 1-4, and OR is an ethoxy or methoxy group; Preferably, the ethoxysilane includes one or a combination of two or more of γ-chloropropyltriethoxysilane, dimethyldiethoxysilane, dipropyldiethoxysilane, diisopropyldiethoxysilane, isobutyldiethoxysilane, dibutyldiethoxysilane, cyclohexylmethyldiethoxysilane, cyclohexylisopropyldiethoxysilane, cyclopentylisobutyldiethoxysilane, cyclopentylisopropyldiethoxysilane, cyclopentylbutyldiethoxysilane, cyclopentylpropyldiethoxysilane, dicyclopentyldiethoxysilane, diphenyldiethoxysilane, phenyltriethoxysilane, methyltriethoxysilane, butyltriethylsilane, isobutyltriethoxysilane and vinyltriethoxysilane; Preferably, the methoxysilane includes one or a combination of two or more of γ-chloropropyltrimethoxysilane, dimethyldimethoxysilane, dipropyldimethoxysilane, diisopropyldimethoxysilane, isobutyldimethoxysilane, dibutyldimethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexylisopropyldimethoxysilane, cyclopentylisobutyldimethoxysilane, cyclopentylisopropyldimethoxysilane, cyclopentylbutyldimethoxysilane, cyclopentylpropyldimethoxysilane, dicyclopentyldimethoxysilane, diphenyldimethoxysilane, phenyltrimethoxysilane, methyltrimethoxysilane, butyltrimethoxysilane and isobutyltrimethoxysilane.
3. The preparation method according to claim 1, characterized in that: In S3, the pre-loading titanium reaction is carried out at 20-0°C for 1-3h; Preferably, the molar ratio of the titanium compound to the magnesium compound is 2 to 30:1; Preferably, the titanium compound includes one or more of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, tetrabutoxytitanium, and tetraethoxytitanium; more preferably, it is titanium tetrachloride.
4. The preparation method according to claim 1, characterized in that: In said S2, a crystallization accelerator is also added; Preferably, the molar ratio of the crystallization promoter to the active magnesium halide is 0.05 to 1:1; Preferably, the crystallization promoter is an acid anhydride crystallization promoter; preferably, the crystallization promoter includes one or a combination of two or more of norbornene anhydride, phthalic anhydride, and maleic anhydride.
5. The preparation method according to claim 1, characterized in that: In S1, the molar ratio of the active magnesium halide to the alcohol is 1:1 to 5; preferably 1:2 to 3; Preferably, the ratio of the active magnesium halide to the hydrocarbon solvent is 1 mol: 0.2-1.0 L; Preferably, the hydrocarbon solvent is a C4-C18 aliphatic hydrocarbon, more preferably a C6-C12 aliphatic hydrocarbon; Preferably, in S1, the alcohol comprises a C2-C16 fatty alcohol; preferably comprises one or a combination of two or more of ethanol, propanol, butanol, hexanol, 2-methyl alcohol, n-heptanol, isooctyl alcohol, and n-octanol; Preferably, in S1, the molar ratio of the ethoxysilane to the methoxysilane is 7-9:1-3.
6. The preparation method according to claim 1, characterized in that: In S4, the temperature of the supplementary reaction is 90-110° C.; Preferably, the molar amount of the alkoxysilane added in S4 is 1 / 5 to 1 / 3 of the alkoxysilane added in S2.
7. A solid titanium catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. An ultra-high molecular weight polyethylene, characterized in that: The solid titanium catalyst according to claim 7 is used for catalytic preparation, and the preparation conditions include: reaction temperature of 40 to 90°C, preferably 60 to 85°C, pressure of 0.1 to 1 MPa, preferably 0.2 to 0.8 MPa; The ultra-high molecular weight polyethylene satisfies one or a combination of two or more of the following conditions: The viscosity average molecular weight is 200,000 to 1 million; The intrinsic viscosity is 4 to 10 dl / g; Ash content is 150-200ppm; Bulk density is 0.45~0.60g / cm 3 ; The average particle size is 100-200μm.
9. A lithium battery separator, characterized in that: Obtained by processing the ultra-high molecular weight polyethylene described in claim 8.
10. A lithium battery, characterized in that: A lithium battery separator comprising the lithium battery separator according to claim 9.
Citation Information
Patent Citations
Ultrahigh-molecular weight ethylene polymer powder and molded article using the ultrahigh-molecular weight ethylene polymer powder
CN110982000A
Catalyst for manufacturing polyethylene with ultra-high to ultra-high molecular weight
CN113831436A